2019
DOI: 10.1038/s41598-019-38867-2
|View full text |Cite
|
Sign up to set email alerts
|

The circulating form of neprilysin is not a general biomarker for overall survival in treatment-naïve cancer patients

Abstract: The transmembrane zink-metalloendopeptidase neprilysin (NEP) is implicated in cardiovascular disease but also tumor biology. The aim of the study was to investigate the relationship of circulating NEP (cNEP) levels with established cardiovascular biomarkers and its effect on overall survival in an unselected cohort of treatment-naïve cancer patients. 555 consecutive cancer patients prior anticancer therapy were enrolled prospectively. NEP levels were determined alongside routine laboratory parameters, establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…This altered maternal metabolic and pro-inflammatory environment translates also to the fetal circulation, as fetal insulin resistance, increased cord blood TNFα, and CRP arise [25][26][27][28]. However, whilst insulin resistance and inflammatory status are associated with elevated MME in adults [16][17][18], other mechanisms seem to account for MME regulation in the fetal compartment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This altered maternal metabolic and pro-inflammatory environment translates also to the fetal circulation, as fetal insulin resistance, increased cord blood TNFα, and CRP arise [25][26][27][28]. However, whilst insulin resistance and inflammatory status are associated with elevated MME in adults [16][17][18], other mechanisms seem to account for MME regulation in the fetal compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors of the altered metabolic and pro-inflammatory environment contribute to this upregulation-in vitro experiments revealed that hyperglycemia and hyperlipidemia increase MME production in endothelial cells [15]. Additionally, the correlation of circulating MME levels with CRP (C-reactive peptide) reveals the susceptibility of MME to the pro-inflammatory environment, and pro-inflammatory mediators such as IL-β1 (interleukin β1) and TGFβ (transforming growth factor β) increase MME in various cell types [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…One study measured NP in an unselected cohort of 600 successive newly diagnosed cancer patients to their large oncology service. An elevated baseline NT-proBNP pre-oncology treatment was a signifcant predictor of mortality risk: hazard ratio 1.54 (95% CI 1.24 to 1.90, p<0.001) with a Kaplan-Meier survival rate of 67% versus 49% (in patients with normal NT-proBNP, p<0.001) at a median of 25 months follow-up [94].…”
Section: Natriuretic Peptidesmentioning
confidence: 96%
“…41 Nevertheless, there were no differences in plasma NEP concentrations for distinct tumour entities or stages, whereas it seemed to be a risk factor for mortality in myelodysplastic disease. 42 It seems that plasma NEP concentrations are poor predictors of outcomes in HF and other diseases and might not be ideal biomarkers.…”
Section: Non-membrane-associated Serum/ Plasma Neprilysin Concentrationsmentioning
confidence: 99%
“…[ 41 ] Nevertheless, there were no differences in plasma NEP concentrations for distinct tumour entities or stages, whereas it seemed to be a risk factor for mortality in myelodysplastic disease. [ 42 ]…”
Section: Neprilysin As a Biomarkermentioning
confidence: 99%